Society as a Code: Bentham and the Fabric of Order. Issue 1 (2nd January 2016) - Rudan, Paola
SUMMARY: The essay argues that Jeremy Bentham played a major role in the transitional process between the eighteenth and the nineteenth centuries leading to the 'discovery' or 'invention of society' as an order, i.e., as an autonomous object of knowledge. By comparing Bentham's discourse with those developed by select protagonists of that transition, particularly Ferguson, Sieyès, and Mirabeau, it is shown how society emerges as the logical and historical space of a set of relationships that affects both the rationalisation and the practice of government. In contrast with Michel Foucault's interpretation of Bentham's role in the genealogy of neoliberalism, recently developed by Pierre Dardot and Christian Laval, this paper suggests that 'the new governmental reason' rose from within the discourse of law. Consequently, the problem of 'constitution' was not left behind by the epistemological change of the eighteenth century, as they argue. Rather, the scientific and political understanding of society as a code became the base for an innovative conception of both law and politics.